2017
DOI: 10.1139/cjz-2016-0038
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal niche partitioning and coexistence of amphimictic and parthenogenetic lineages of Heterocypris barbara (Crustacea: Ostracoda)

Abstract: Sympatry of amphimictic and parthenogenetic lineages in species with mixed reproductive systems is rarely observed in nature. On Lampedusa Island (Pelagie Islands, Italy), amphimictic and parthenogenetic lineages of Heterocypris barbara (Gauthier and Brehm, 1928) co-occur in a temporary pond. Their sympatric persistence calls for an ecological differentiation. We investigated the role of seasonal variation of temperature and photoperiod conditions by two different approaches: microcosms set up by inundation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
(93 reference statements)
1
4
0
Order By: Relevance
“…Our results strongly suggest that ecological differentiation may be a cornerstone to coexistence of the sexuals and asexuals forms in Venturia canescens . Our conclusion is congruent with previous studies reporting, in several taxa, differences in habitat preferences and in responses to environmental conditions between closely related sexual and asexual strains: in plants (dandelions, Meirmans, Meirmans & Kirkendall, 2012 ), insects (aphids, Simon, Rispe & Sunnucks, 2002 ; Gilabert et al, 2014 ), crustaceans ( Rossi et al, 2017 ) and fish ( Schenck & Vrijenhoek, 1986 ). Nevertheless, to firmly conclude about the involvement of ecological differentiation on coexistence of both reproductive modes in V. canescens , further investigations are needed to experimentally test, as done by Lehto & Haag (2010) in Daphnia pulex , whether the relative fitness of the sexual and asexual wasps depends on ecological conditions, that is, whether sexuals outperform asexuals in the field and asexuals outperform sexuals in building conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Our results strongly suggest that ecological differentiation may be a cornerstone to coexistence of the sexuals and asexuals forms in Venturia canescens . Our conclusion is congruent with previous studies reporting, in several taxa, differences in habitat preferences and in responses to environmental conditions between closely related sexual and asexual strains: in plants (dandelions, Meirmans, Meirmans & Kirkendall, 2012 ), insects (aphids, Simon, Rispe & Sunnucks, 2002 ; Gilabert et al, 2014 ), crustaceans ( Rossi et al, 2017 ) and fish ( Schenck & Vrijenhoek, 1986 ). Nevertheless, to firmly conclude about the involvement of ecological differentiation on coexistence of both reproductive modes in V. canescens , further investigations are needed to experimentally test, as done by Lehto & Haag (2010) in Daphnia pulex , whether the relative fitness of the sexual and asexual wasps depends on ecological conditions, that is, whether sexuals outperform asexuals in the field and asexuals outperform sexuals in building conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, under climate change conditions, variations in rainfall patterns, temperature and evaporation increase, are expected to increase conductivity levels [36,64,82]. In Heterocypris, high conductivity delayed hatching of resting eggs from an egg bank [83]. In contrast to an increase of temperature, increasing of conductivity levels may reduce the hatching rate and the depletion of the egg bank or may reduce growth rates and fecundity of freshwater invertebrates [36].…”
Section: Discussionmentioning
confidence: 99%
“…Carvalho and Crisp (1987) demonstrated that five of the dominant genotypes in their system were seasonal specialists, favored in summer, fall, or winter, and that this pattern was consistent across multiple locations within a lake and across multiple years. In ostracods, this seasonal resource partitioning is thought to allow for coexistence among lineages (Rossi et al, 2017). There are a vast number of seasonally changing variables that could be responsible for the seasonal turnover of genotypes, with resource availability being just one possibility.…”
Section: Re Sultsmentioning
confidence: 99%